MANAJEMEN PENDIDIKAN KARAKTER DALAM MEMBANGUN BUDAYA SEKOLAH - Anam, Khoirul (PEDAGOGY, 2017)
Management of character education in building a culture of schools include: Planning character education has an urgent position in building a school culture with menitiktekankan on activities that character, habituation and installation slogans. Organizing character education carried out by the direct command of the leaders of educational institutions, but it should be demanded active participation of the academic community of the institutions. Implementation of character education is implemented in accordance with the scenarios that have been planned, under the responsibility of each and every person in charge of carrying out the task as well as possible with the various advantages and disadvantages of each. Control measures implemented code execution pendidikaan integrated by all interested parties, is ongoing or continue and shall be responsible for himself before others and before the One Who is Aware.